EFFECTIVENESS OF AJWA DATE SEED EXTRACT EFFERVESCENT TABLETS (Phoenix dactylifera L.) AGAINST MICROORGANISMS ON ACRYLIC RESIN - Amiruddin, Maqhfirah; Pertiwisari, Amanah; Vebryansyah, Alhady Putra; Nurasisa Lestari, Nurasisa; Sembiring, Ira Asnita (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Suboptimal denture cleaning methods present a problem for denture users, leading to the buildup of bacteria and fungi on the denture base. Streptococcus mutans is a bacterium involved in plaque formation, while Candida albicans is the most abundant fungus in the oral cavity. Ajwa date seeds, with a concentration of 3.25%, have been shown to strongly inhibit the growth of both bacteria and fungi. This study utilizes effervescent tablets containing Ajwa date seed extract. Purpose: The aim of this study is to evaluate the effect of immersing effervescent tablets containing Ajwa date seed extract on the growth of Streptococcus mutans and Candida albicans on acrylic resin. Methods: The research employed a True Experimental design with a Post Test Only Control Group. A spectrophotometer was used to measure bacterial and fungal growth, and various concentrations of the extract in effervescent tablet preparations were tested. Alkaline peroxide was used as a positive control, while distilled water served as a negative control. Results: The One-Way ANOVA test showed that the smallest bacterial count was observed in the alkaline peroxide group (0.008) and the 13% extract concentration group (0.011). The largest bacterial count was observed in the distilled water group (0.065). The smallest fungal count was also observed in the alkaline peroxide group (0.022), while the largest fungal count was recorded in the distilled water group (0.210). Conclusion: The One-Way ANOVA test revealed significant differences in the number of bacteria and fungi based on the treatment groups.